Nanomaterials in the workplace : policy and planning workshop on occupational safety and health - Bartis, James T., 1945-; Landree, Eric.; Public Safety and Justice Program (Rand Corporation); Rand Infrastructure, Safety, and Environment (Organization); Rand Corporation; National Institute for Occupational Safety and Health (Santa Monica, CA : RAND, 2006)
What are the challenges the National Institute for Occupational Safety and Health (NIOSH) and related federal agencies face when allocating limited resources so that worker health and safety go hand in hand with innovation and technical progress? This was the central issue addressed at a workshop on nanotechnology and occupational safety and health hosted by the RAND Corporation on October 17, 2005. The workshop focused on policy and planning issues (as opposed to scientific issues) that are key to understanding the options available to NIOSH in formulating and implementing its strategic objectives to protect the safety and health of workers exposed to nanoscale materials. This document of the conference proceedings draws on discussions during the workshop and places the discussions within a policy framework for further consideration by NIOSH.
Introduction -- Strategic Challenges -- Resources -- Toward Nanotechnology Workplace Safety -- Appendix A: Workshop Participants -- Appendix B: Agenda for Policy and Planning Workshop on Nanotechnology and Occupational Safety and Health
"RAND Infrastructure, Safety, and Environment."
Includes bibliographical references (p. 31-34).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Industrial hygiene; Industrial safety; Nanotechnology -- Health aspects